Effect of Physico-Chemical Changes in Sesame (Sesamum indicum L.) Seeds due to Storage - Bhattacharya, Chitra; Pandey, Bhawana; Paroha, Seema (Asian Journal of Biological and Life Sciences, 2013)
Sesamum is widely spread world and is cultivated for its edible seed and oil. It was made to determine the differences in physicochemical properties of Sesame varieties with different seed coat colours viz white, black, and brown and to assess the possible physicochemical changes after one year of storage. Some of the important physicochemical characters were taken in the present study viz. specific gravity, refractive index, free fatty acid, iodine value, saponification value, unsaponificable matter and peroxide values. These varieties exhibited the same pattern after one year of storage with an increase of 1.38%, in white, 2.10% in brown and 2.50% in black seeded sesame, Iodine value is a useful parameter in studying oxidative rancidity of oils since higher the unsaturation remained almost unchanged after one year of storage in all the three varieties. Saponification value of oils obtained from the fresh harvest samples ranged from 194 to 172 highest was found in black variety and while lowest was found in white variety. But the saponification value increased in stored sample by 9.8% in white 8.2% in black and 5.2% in brown seeded variety, contained in unsaponificable matter have antioxidant is decreases and Peroxide value increased considerably after one year of storage. These data indicates that the physicochemical characteristics of sesame seed reduces after one year storage.